Evaluation of a Medical Residency Program in Gynecology and Obstetrics - Sanchez,Natalia Romano (2020)
Abstract: Introduction: Medical residency in gynecology and obstetrics is unquestionably important in the training of physicians who choose this specialty of the Brazilian Ministries of Health and Education. However, studies evaluating these residency programs are scarce, especially regarding the reflexive qualitative aspects of the research. Therefore, this exploratory and descriptive study aimed to evaluate the current medical residency program in gynecology and obstetrics of the School of Medical and Health Sciences at Pontifícia Universidade Católica de São Paulo (PUC-SP) using a quantitative and qualitative approach. Method: The methodology included a comparative curriculum analysis between the program recommended by the National Committee of Medical Residency until 2018 and the program offered by PUC-SP School of Medical and Health Sciences, as well as a self-administered questionnaire completed by individuals who graduated between 2007 and 2018. Results: The most significant findings of the comparative curriculum analysis include discrepancies in the percentage arrangement of annual workload, indicating an overload of on-call duty hours, and unequal distribution of internships. The questionnaire response rate was 66% (41 of 62 participants). Most respondents were women (n=32, 78%), who worked mainly in the cities of Sorocaba (n=21, 43.7%) and São Paulo (n=10, 21%). Most medical graduates were partially satisfied with the program (n=34, 82.9%). Some responses also matched the findings of the comparative curriculum analysis, such as dissatisfaction with the number of gynecological surgical procedures performed (n=39, 95.1%). Regarding the content analysis of open-ended answers, categorized according to Bardin, the graduates appreciated activities in obstetrics, and the most relevant criticisms were related to fewer hours assigned to certain activities, especially those devoted to gynecological surgical practices and theoretical activities. Conclusions: Based on the findings, suggestions were proposed and accepted by the managers for changes that should have a positive impact on the medical residency program. This research contributes to the diagnostic evaluation of a traditional medical residency program in Brazil, proposes improvements, and uses reproducible methods, thus serving as a comparison basis for other studies so that advances can be made in the training of these specialists.